Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw terhadap Kemampuan Literasi Siswa Kelas VI pada Mata Pelajaran Bahasa Indonesia di SDN 76 Tarowang - Nur Inaya B; Mega Widya Lestari; Besse Syukroni Baso; Haris Haris (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of applying the Jigsaw cooperative learning model on students’ literacy skills in the Indonesian language subject for sixth-grade students at SDN 76 Tarowang. The research employed a Quasi-Experimental Design with a Pretest–Posttest Design. The sample consisted of 17 students who participated in the learning process using the Jigsaw model. Data were collected through literacy skill tests administered before and after the treatment.The results showed that the average pretest score of 28.47 increased to 56.41 in the posttest, indicating an improvement of 27.94 points. The Shapiro–Wilk normality test confirmed that the data were normally distributed (pretest Sig. = 0.513; posttest Sig. = 0.336). Furthermore, the Paired Sample t-test revealed a t-value of 7.180 with a significance level (Sig. 2-tailed) = 0.000 (< 0.05), indicating a significant difference between pretest and posttest scores. These findings demonstrate that the implementation of the Jigsaw cooperative learning model has a significant positive effect on students’ literacy skills. This model effectively engages students in reading comprehension, summarizing information, and communicating ideas collaboratively.